(Microfinance and its impact on the standard of living - Case study - (Some cities of West Kordofan State - Sudan, during the period from 2009 to 2017 - Bilal, Ibrahim Abdul Rasool Mohammed; Saadallah, Hawa Abdullah Bilal; Alselik, Amina Abdelkader (Journal of Economic, Administrative and Legal Sciences, 2017)
This research comes under the title: Micro-finance and its impact on the living standard during the period 2009-2017 (A case study: AL Fula, AL Nuhud and AL Khuwai towns in West Kordufan State(WKS)).The main obgectives are, to find out the impact of income which received from various projecs financed through micro-finance institutions in WKS on some economic and social indicators,beside study of different obsticales and provide solutions to improve micro-finance projecs in this Estate. The study adopted descriptive and analytical statistical method to study the case, hence the study concoluded with several findings such as,micro-finance provide great opportunities to encrouge economic activities through creating of other sub-activities,increasing income of many individuals beside provides work opportunities and enhancement of social empowerments more specifically for whomens. The study recommended the important of developing micro-finance services , increasing government efforts to develop credit funds and other social institutions , modificaions of returns on micro-finance for banks,dissemination of culture ,increasing awareness and provides training courses to link customers with banks and other financial institutions.